Association between immune-related adverse events and immunotherapy efficacy in non-small-cell lung cancer: a meta-analysis - Lin, Li; Liu, Yu; Chen, Chen; Wei, Anhua; Li, Wei (Frontiers in Pharmacology, 2023)
Objective: Our study was aimed to identify potential correlations between anti-tumor efficacy and immune-related adverse events (irAEs) in non-small cell lung cancer (NSCLC). Methods: We conducted a comprehensive search of online electronic databases until March 2023 to identify any association between irAEs and immune checkpoint inhibitor (ICI) efficacy in NSCLC. We used meta-analysis Revman 5.3 software to calculate pooled results. Result: Our meta-analysis, which included 54 studies, revealed that patients who experienced irAEs achieved a significantly higher objective response rate (ORR) (P＜0.00001), longer progression-free survival (PFS) (P＜0.00001), and overall survival (OS) (P＜0.00001) than those who did not experience irAEs. In addtion, patients with ≥2 irAEs had better PFS, while no significant difference was seen between patients with squamous cell carcinoma and those without it. Subgroup analysis of irAE types indicated that any irAEs, thyroid dysfunction, gastrointestinal, skin, and endocrine irAEs were associated with better PFS and OS. However, no significant difference was found in patients with pneumonitis and hepatobiliary irAEs. Conclusion: Our study showed that the occurrence of irAEs was a strong predictor of survival efficacy in patients with NSCLC treated with ICIs. Specifically, patients who experienced ≥2 irAEs and those with thyroid dysfunction, gastrointestinal, skin, and endocrine irAEs, achieved a better survival benefit.